Preparation and characterization of cellulose nanoparticles and nanocomposites films derived from printed paper wastes - Voon, Lee Ken (Universiti Malaysia Sarawak, UNIMAS, 2013)
The increasing amount of paper wastes generated around the world has caused disposal problems to our environment. Paper wastes are one of major cellulosic waste materials which include printed office papers, newspapers, magazines and books. In this study, cellulose was extracted from printed paper waste and then converted into cellulose nanoparticles and nanocomposite films. The paper wastes underwent pretreatment, dissolution and regeneration processes under controlled conditions. The nanoprecipitation technique was used to regenerate cellulose nanoparticles from dissolved cellulose solution. Particle sizes of cellulose nanoparticles were controlled by varying parameters such as cellulose concentration and addition of surfactant. The sago starch and cellulose nanoparticles were used to form green nanocomposite film. Both cellulose nanoparticles and nanocomposite films prepared from printed paper wastes were characterized by SEM and FTIR.